(untitled) (The Review of Diabetic Studies, 2023)
Islet antigens are presented by human leukocyte antigen (HLA) class I and II molecules and are recognized by CD8+ and CD4+ autoreactive T cells in type 1 diabetic individuals. Early identification of individuals at risk for the disease by detection of these antigens and the autoreactive cells themselves is essential for understanding pathogenesis and for intervention at an early stage to prevent ongoing beta-cell destruction. However, the methods of identifying autoimmune development at an early stage have appeared to be limited because of the heterogeneity of the disease. The appearance of autoantibodies in preclinical type 1 diabetes mellitus (T1DM) does not follow specific patterns and depends on patient characteristics such as age. Also, results obtained with cytokine assays revealed that the number of islet antigen-responsive T cells present in the pool of peripheral blood mononuclear cells (PBMC) of non-diabetic individuals is highly variable and can be similar to that assayed in diabetics. Therefore, new identification and detection methods are needed. In this context, the use of HLA epitopes to generate stable HLA epitope tetramers has recently proved to be a promising approach to the detection of autoreactive T cells in antigen-stimulated PBMC cultures from diabetic and pre-diabetic subjects. HLA class II tetramers have been found to be capable not only of detecting TCRαβ of different avidities for a common ligand, e.g. GAD65555-567(mimitope), but also of inducing apoptosis in lymphocytes with high TCRαβ avidity for this ligand. This observation even opens up a potential application of HLA class II tetramers as therapeutic agents for immune intervention in T1DM.